STRUCTURAL PERFORMANCE OF MASONRY BLOCKS REINFORCED WITH PLANTAIN PSEUDO-STEM FIBER (Malaysian Journal of Civil Engineering, 2018)
Renewable fiber derived from plantain pseudo-stem was used as reinforcing material in improving selected engineering properties of masonry blocks. The blocks were made from two sets of mixtures: the first, which acts as reference sample, consists of cement, lime, and sand in the ratio of 1: 0.25: 6, respectively with water-cement ratio of 0.52; the second set consists of the composition of the reference sample in addition to the inclusion of varied weight percentages (1 - 4%) of plantain pseudo-stem fiber replacing the binders. The wet mixtures were manually cast into block of 150 mm cube size for tensile splitting and water absorption tests; and 115 mm x 110 mm x 80 mm size for compressive strength and density tests. The tensile splitting strength of the masonry blocks recorded its optimal value of 0.66 N/mm2 at 28 days with 3% weight fiber content. The compressive strength values were observed to decrease as the fiber content increases; however, with 4% weight fiber content the compressive strength values were noted to be higher than the minimum strength specified for both non-load bearing and load bearing walls. The density and water absorption were found to decrease as the fiber content increases. It was observed that all the investigated properties, except water absorption, have their values increases with curing time. The study therefore concluded that the inclusion of 4% weight plantain pseudo-stem fiber, having satisfied the minimum requirements of the properties investigated, is adequate for the masonry blocks production.